2019
DOI: 10.3389/fmicb.2019.01018
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacteria and Cyanobacteria Diversity in Terrestrial Antarctic Microenvironments Evaluated by Culture-Dependent and Independent Methods

Abstract: Bacterial diversity from McMurdo Dry Valleys in Antarctica, the coldest desert on earth, has become more easily assessed with the development of High Throughput Sequencing (HTS) techniques. However, some of the diversity remains inaccessible by the power of sequencing. In this study, we combine cultivation and HTS techniques to survey actinobacteria and cyanobacteria diversity along different soil and endolithic micro-environments of Victoria Valley in McMurdo Dry Valleys. Our results demonstrate that the Dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 149 publications
(223 reference statements)
3
40
0
Order By: Relevance
“…In agreement, the principal components analysis (PCA) applied to the environmental variables (Table S1) indicates that sample 54 was distinguished from others by being associated with high total organic matter and water content ( Figure S2). A previous study from our team [47] has revealed that in samples with higher water availability, from McMurdo Dry Vallleys, Antarctica, Actinobacteria dominance was replaced by other phyla, such as Cyanobacteria. Similarly, sample 54 harbors a lower relative abundance and richness of Actinobacteria ( Figure 4A) which might be related to the observed shift in KS/AD diversity ( Figure 2).…”
Section: Diversity Of 16s Rrna Gene Ks and Ad Domains In The Maxwellmentioning
confidence: 81%
“…In agreement, the principal components analysis (PCA) applied to the environmental variables (Table S1) indicates that sample 54 was distinguished from others by being associated with high total organic matter and water content ( Figure S2). A previous study from our team [47] has revealed that in samples with higher water availability, from McMurdo Dry Vallleys, Antarctica, Actinobacteria dominance was replaced by other phyla, such as Cyanobacteria. Similarly, sample 54 harbors a lower relative abundance and richness of Actinobacteria ( Figure 4A) which might be related to the observed shift in KS/AD diversity ( Figure 2).…”
Section: Diversity Of 16s Rrna Gene Ks and Ad Domains In The Maxwellmentioning
confidence: 81%
“…Trace gas oxidation may explain why Actinobacteria is the dominant bacterial phylum in desert soils. The relative abundance of this phylum increases with aridity (147,148), and it typically accounts for 30 to 80% of the microbial community in hyper-arid sites (7,13,132,145,147,149) (Fig. 1).…”
Section: Continual-energy-harvesting Hypothesismentioning
confidence: 99%
“…Isolate LEGE Z‐009 was obtained from an isolation process originally intended for isolating cyanobacteria (Rego et al. ). An aliquot of the endolithic sample was washed and centrifuged three times (4500 g , 3 min) with nitrogen‐free BG11 0 medium (Rippka ).…”
Section: Methodsmentioning
confidence: 99%